Decrease in the incidence of threatened preterm labor after implementation of transvaginal ultrasound cervical length universal screening. (3rd June 2019) - Navathe, Reshama; Saccone, Gabriele; Villani, Michela; Knapp, Jacquelyn; Cruz, Yury; Boelig, Rupsa; Roman, Amanda; Berghella, Vincenzo
Abstract: Background: It is unknown if universal second-trimester transvaginal ultrasound (TVU) cervical length (CL) screening in asymptomatic women with singleton gestations and no prior spontaneous preterm birth (SPTB) affects the incidence of symptoms of preterm labor (PTL) later in pregnancy. Objective: To evaluate the incidence of threatened PTL before and after the implementation of universal second trimester TVU CL screening. Study design: This was a retrospective cohort study of all consecutive singleton gestations without prior SPTB presenting to obstetric triage for threatened PTL between 23 0/7 and 33 6/7 week in 2011 (1 January–31 December), and in 2014 (1 January–31 December) at Thomas Jefferson University Hospital (TJU) (Philadelphia, PA). These 2 years were chosen as a new protocol for universal TVU CL screening was started on 1 January 2012. This protocol involved one measurement of TVU CL in all singleton gestations without a prior SPTB at 18 0/7 − 23 6/7 week, the time of the "anatomy" scan. Women with prior SPTB were excluded from this study. The primary outcome included the incidence of threatened PTL, defined as the number of women with singleton gestations without prior SPTB who presented with threatened PTL to our labor and delivery (L&D) triage unit annually, divided by the total number of annual deliveries of women with singleton gestation without prior SPTB. Secondary outcomes were the incidence of PTL, defined as the number of women with singleton gestations without prior SPTB admitted for PTL annually divided by the total number of annual deliveries of women with singleton gestation and without prior SPTB; and length of stay in the hospital. We aimed to compare primary and secondary outcome in the "2011" versus the "2014" group. Results: In 2011, there were a total of 1745 deliveries at TJU, of which 1550 (88.8%) were singletons without prior SPTB. In 2014, there were a total of 1924 deliveries at TJU, 1751 (91.0%) were singletons without prior SPTB who were offered universal TVU CL screening. One hundred and seventy-two women with singletons without prior SPTB presented in L&D triage unit in 2011; and 118 women with singletons without prior SPTB presented in L&D triage unit in 2014. There were significant decreases in the incidence of threatened PTL from 11.1% (172/1550) in 2011 to 6.7% (118/1751) in 2014 ( p < .001), as well as in the rate of admission for PTL from 2.3% (35/1550) to 1.4% (24/1751), respectively ( p = .04). Length of stay was not significantly different between the two groups. Conclusion: The introduction of a universal TVU CL screening program in women with singleton gestations without a history of SPTB is associated with a reduction in the frequency of threatened PTL and admission for PTL. Key Message: The introduction of a second trimester universal transvaginal ultrasound (TVU) cervical length (CL) screening program in women without a history of spontaneous preterm birth (SPTB) is associated with a reduction in the incidence of threatened preterm labor (PTL) and admission for PTL.